BDNF mRNA Expression in Leukocytes and Frontal Cortex Function in Drug Use Disorder - Anders, Quézia Silva; Ferreira, Leonardo Villaverde Buback; Rodrigues, Livia Carla de Melo; Nakamura-Palacios, Ester Miyuki (Frontiers in Psychiatry, 2020)
BDNF is a neurotrophin involved in neuroplastic changes in reward circuits caused by drugs of abuse and it has been associated with different behavioral changes in drug use disorders, such as drug sensitization, craving and relapses. These neuroplastic changes affect the prefrontal cortex functions which can be briefly measured through cognitive tests such as Frontal Assessment Battery (FAB). In this study we investigated the BDNF mRNA expression in peripheral blood leukocytes of drug addicted patients after drug detoxification treatment using real-time PCR approach and related it to FAB performance. BDNF mRNA expression was higher by 2.25-fold in CUD patients and by 2-fold in the AUD patients when normalized to controls and these values were found to be associated with FAB scores. This is the first study to evaluate the BDNF mRNA expression in leukocytes and its relationship to the FAB scores in alcohol an crack-cocaine use disorder patients.